E-learning como mecanismo de apoyo al aprendizaje de los estudiantes de la Unidad Educativa La Ronda del cantón Babahoyo provincia de Los Ríos. - Alvario Alvario, Keny Wellington (2023)
This research aims to demonstrate that E-learning can serve as a support mechanism to improve the learning of students at the La Ronda Educational Unit, located in the Babahoyo Canton of the Province of Los Ríos; therefore, it seeks to demonstrate the effectiveness of E-learning in the teaching-learning process of students by improving their grades and the satisfaction of both students and teachers. The research found that most students have regular access to electronic devices with internet, which makes them suitable to use internet platforms to support their learning; in addition, teachers expressed interest in using this type of tools in the classroom in order to improve the quality of teaching and learning. The results of the study revealed that the implementation of this tool resulted in a significant improvement in student learning, as evidenced by the comparison of the grades obtained in the previous period; therefore, both students and teachers expressed their satisfaction with the use of the platform, finding it useful for learning and teaching, respectively. However, despite the benefits offered by E-learning, some challenges were identified in its implementation; in this sense, it is required to improve Internet connectivity and provide additional training to students and teachers, in order to ensure the effective use of this mechanism; in short, although the same can be an effective tool to support student learning, it is essential to address these challenges and provide adequate training to users.